(untitled) (Ius Novum, 2022)
The article aims to analyse disciplinary penalties that can be imposed on a student for disciplinary offences, as well as to draw attention to a controversial issue of indicating determinants of their imposition. The doubts presented in the article that concern the ‘disciplining’ nature of some disciplinary penalties (and even uselessness of one of them) justify de lege ferenda the need to remodel the present catalogue of them. Having noticed that the legislator did not decide to directly determine recommendations for shaping disciplinary penalties for students in the provisions of Act of 1 July 2018: Law on higher education and science, the author presents the opinion that in order to make it possible (for members of the adjudicating panel of a disciplinary commission and sometimes also a rector) to avoid accusations of inevitable arbitrariness in the matter, it would be necessary to make reference to relevant provisions of Criminal Code.